KOMPAKS Community Communication Network in Cat Care - Bahrul Alam; Ainur Rochmania (Universitas Muhammadiyah Sidoarjo, 2022)
The study aims to describe the KOMPAKS community communication network in cat care. The method used in this study is quantitative descriptive with communication network analysis techniques. The population of this study is the KOMPAKS Community. Snowball Sampling technique for sampling while data retrieval using questionnaires and interviews is not structured. Data analysis techniques use communication network techniques with the help of the UCINET 6 application. The result of this study is, the first pattern of communication network structure formed in the Kompaks community is the structure of the Roda communication network. Both roles of communication network structure in the KOMPAKS Community found roles, neglected. Third, in this study, there are no clicks because the terms and conditions on the click do not have a KOMPAKS Community communication network in cat care. The four leaders of the opinion that there are 6 people in the network have an important role in influencing and increasing the participation of community members in cat care. Fifth in this study there are 4 types of innovation adopters in research, namely, innovator, early adopter, early majority, late majority.